Solution combustion synthesis of ZnO doped CuO nanocomposite for photocatalytic and sensor applications - A. Naveen Kumar; M. Balakrishna; Usha Desai; R. Rakshith; K. M. Ambika; P. Soumya; C. R. Ravikumar; S. Senthil Vadivu; Nithesh Naik (Scientific Reports)
Abstract ZnO-doped CuO nanocomposites (CuO-ZnO NPs) of 1, 3, and 5 mol% were prepared by the solution combustion method using ODH as a fuel (Oxlyl-hydrazide) at 500 °C and calcining at 1000 °C for two hours and the Structural, photocatalytic, and electrochemical properties were investigated by experimental and theoretical methods. X-ray diffraction (XRD) patterns revealed a crystallite size (D) range of 25 to 31 nm for pure CuO and 1, 3, and 5 mol% CuO-ZnO NPs. According to calculations, the optical energy band gap (Eg) of the NPs is between 2.1 and 2.5 eV. Under UV light irradiation, the photocatalytic degradation of CuO + 3%ZnO NPs on Congo Red (CR) and Methylene Blue (MB) dye was assessed under the influence of UV light. The degradation efficiency increased with the catalyst dosage (10 − 60 mg L− 1). At a concentration of the catalyst of 60 mg, the degradation efficiency can even reached 70% after 120 min. The electrochemical properties of the prepared NPs were studied using cyclic voltammetry and electrochemical impedance spectroscopy (EIS). Solutions of glucose and ascorbic acid were effectively sensed using modified carbon paste electrodes. These innovative results can be considered for the expansion of novel resources to scale for dual applications in the areas of photocatalysis and sensors.